ANTIBACTERIAL ACTIVITY TEST OF ETHANOL EXTRACT TEMU KUNCI (Boesenbergia pandurata) AGAINST Streptococcus mutans BACTERIA - Fitri Lestari Mahmudah; Sri Atun (Jurnal Penelitian Saintek, 2017)
The purpose of this study was determined the antibacterial activity on ethanol extract of temukunci (Boesenbergia pandurata Roxb) against Streptococcus mutans bacteria. The subject of this research was the ethanol extract of temukunci. The object of this study was the antibacterial activity of the ethanol extract of temukunci. The research method was disk difussion method by Kirby-Bauer test. The positive control that  used was chloramphenicol. The concentration variations were 0.5 sampai 500 µg/ml. The results show that the ethanol extract of temukunci can inhibit the growth of Streptococcus mutans bacteria. Maximum concentration that can inhibit the growth of Streptococcus mutans bacteria is at concentration 50 µg/ml.